Revealing the Myths in Iphone 14 Advertisement: Semiotics Approach - Aileen Gracesela Sanjaya; Endar Rachmawaty Linuwih; Eka Fadilah (ITScience (Information Technology and Science), 2023)
Semiotics is a branch of science that examines human signs. The semiotic aspects and cases are exciting topics to discuss in interpreting the meaning of advertising because the ambiguous message conveyed in the advertisement may cause difficulties in understanding its meaning among the customers. This research aims to discover the connotative and denotative meanings of the signs in the iPhone 14 advertising video. This study was qualitative research. The data of the study is iPhone 14 advertising video; Action Mode Feature. The data were analyzed with verbal and nonverbal signs according to Saussure's theory (1950) in the form of words, phrases, sentences, sounds, situations, models, motion, and video images of iPhone 14 advertisement and then searched for connotative and denotative meanings according to Barthes' theory (1983). The results revealed that the advertisement aims to create consumer appeal by emphasizing the iPhone 14's luxurious design and the quality associated with the Apple brand. In addition, by featuring Black individuals prominently, the ad sends a message of inclusivity and empowerment, suggesting that success and prestige are attainable by all, regardless of their racial or ethnic background. Therefore, the iPhone 14 positions itself as a symbol of progress, both technologically and socially.